Observation of an unpaired photonic Dirac point - Gui-Geng Liu (Nature Portfolio, 2020)
Observing the photonic analogue of an unpaired Dirac point is hard, as it requires breaking the time-reversal symmetry. Here, the authors use gyromagnetic materials to do that, and thus succeed in observing an unpaired Dirac point in a planar photonic crystal operating at microwave frequencies.